Rancang Bangun Sistem Kasir Berbasis Website Untuk Toko Sembako Dengan Menggunakan Metode Agile - Achmad Anang Firmansyah; Rahmi Rizkiana Putri (INTEGER: Journal of Information Technology, 2026)
The development of information technology has encouraged business owners, including grocery stores, to adopt Point of Sale (POS) systems that improve operational effectiveness and efficiency. This study designs and develops a website-based cashier system for grocery stores equipped with barcode scanner support using the Agile Development method. The system helps manage product stock in real time, process sales transactions, and generate reports while minimizing errors commonly found in manual recording. The development process uses Laravel as the backend framework, Tailwind CSS for the user interface, and PostgreSQL as the database. The Agile method ensures flexibility through iterative cycles and continuous evaluation. System testing uses the black-box method to verify that all functionalities work as expected, along with a feasibility test based on the ISO 9126 standard to evaluate usability, functionality, and efficiency. The results indicate that the system effectively supports grocery stores in managing transactions and inventory while providing accurate and reliable sales reports